A review of the antimicrobial benefits of naturally extracted nanomaterials - S.I, Asiya; Sarangapani, Anandhi (International Journal of Advances in Applied Sciences, 2024)
Nanotechnology finds immense potential due to the unique characteristics of nanomaterials. Though noble metal nanoparticles, particularly gold and silver nanoparticles possess advanced properties their conventional production methods pose environmental hazards. This paper explores the eco-friendly approaches using natural sources for synthesizing gold and silver nanoparticles. Rose and pomegranate extracts were used to synthesize gold nanoparticles. Evaluation using ultraviolet-visible (UV-Vis) spectroscopy confirmed the nanoparticle formation, and Fourier transform infrared spectroscopy (FT-IR) analysis recognized the presence of plant-derived compounds for stabilizing these particles. In-depth observations of their size and form were provided using electron microscopy, and these findings were aligned with the inferences made from the UV-Vis data. Silver nanoparticles were produced using Ocimum gratissimum leaf extract (OGE), exhibiting dose-dependent antimicrobial effects against bacterial strains. A comparative analysis demonstrated the distinct antibacterial characteristics of silver and gold nanoparticles against several bacterial strains. These nanoparticles demonstrated enhanced inhibitory effects when employed in combination with antibiotics, suggesting the possibility of dealing with antibiotic resistance. The study presents opportunities for producing nanomaterials with minimal impact on the environment and for addressing antibiotic resistance. Further research can enhance the process and find more useful applications as this green synthesis approach can bring about significant improvements in many areas.